"Action Counseling" Intervention for Families in Bosnia-Herzegovina. (13th May 2015) - Toffle, Mary Ellen
Abstract: The Bosnian War was one of the most destructive wars to civilian populations in the history of humanity. Bosnia-Herzegovina has been referred to as a "spectre of a lost future" (Kurtovic, 2014 ). Associazione Fabio Vita nel Mondo ONLUS (AFVM) is an Italian organization that has been carrying out humanitarian operations since 2003. It is fighting hard to eliminate that "spectre". This paper reports the successful counseling work of the Associazione Fabio Vita nel Mondo in Konijc, (Bosnia-Herzegovina) which has prevented many children from going to orphanages. Both trained volunteers and professional counselors assist families. At this time all of the families in the program have been able to keep their children. Further expansion of the program is necessary to encompass other areas of Bosnia-Herzegovina and a larger team of local social workers should be developed.